English translations of Mencius from three different centuries: a progression to more gender-neutral language - Lai, Lanlan; Emily, Lau; Hijjo, Nael (Penerbit Universiti Kebangsaan Malaysia, 2025)
Mencius’ teachings, deeply entrenched in the male-dominated discourse of ancient China, have historically been interpreted from a masculine viewpoint. However, the rise of the feminist movement and advancements in global communication have significantly expanded the audience for Mencius’ philosophy. Concurrently, the English language, influenced by feminist perspectives, has been evolving towards a more gender-neutral style. Against this backdrop, this study explores how translators from three different centuries interpret the unmarked gender language in Mencius. The research adopts a socio-cognitive approach to examine how the linguistic representations link to the cognitive schemas in translation studies with the aid of corpus. The parallel corpus comprises one ST and three TTs (Bloom, 2009; Legge, 1895; Zhao et al., 1999). The research finds that Zhao et al. and Legge prefer generic masculine words. In contrast, Bloom opts for gender-neutral words to interpret the gender-unspecific words in Mencius. This change from an androcentric to a gender-neutral language style reflects the evolving social norms and the translator's subjectivity in challenging or reinforcing prevailing gender stereotypes. The entrenched principle of "MALE-As Norm" deeply influences the stereotypes and cultural schemas that affect how translators behave. This can trigger automatic cognitive schemas, which, in turn, affect the translational choices in selecting generic masculine words. This research underscores the potential of corpus analysis to enrich the study of translation style from a socio-cognitive perspective. The socio-cognitive approach provides a robust theoretical framework, contributing to a nuanced understanding of the complexities of translation style through the interdisciplinary lens of cognition and translation.